FEE, Gordon D. Paulo, o Espírito e o povo de Deus. Campinas: United Press Ltda, 1987. 222pp. - Müller, Waltraut (Vox Scripturae - Revista Teológica Internacional, 2004)
FEE, Gordon D. Paulo, o Espírito e o povo de Deus. Campinas: United Press Ltda, 1987. 222pp.